Trends in and Factors Associated With Episiotomy in the Setting of Nonoperative Vaginal Delivery, 2000–2018. Issue 1 (January 2022) - Logue, Teresa C.; Wen, Timothy; Arditi, Brittany; Huang, Yongmei; Wright, Jason D.; D'Alton, Mary E.; Friedman, Alexander M.
Abstract : Use of episiotomy during nonoperative vaginal deliveries decreased markedly over the 2000–2018 study period.